Brief-stimulus presentations on multiform tandem schedules - Reed, Phil (1994)
Three experiments examined the influence of a brief stimulus (a light) on the behavior of food-deprived rats whose lever pressing on tandem schedules comprising components of different schedule types resulted in food presentation. In Experiment 1, either a tandem variable-ratio variable-interval or a tandem variable-interval variable-ratio schedule was used. The variable-interval requirement in the tandem variable-ratio variable-interval schedule was yoked to the time taken to complete the variable-ratio component in the tandem variable-interval variable-ratio schedule, and the length of the variable-interval component in the latter schedule was yoked to the variable-ratio component in the former schedule. If a brief stimulus occurred following completion of the first component, then behavior was differentiated in the two components; subjects responded more quickly in the variable-ratio than in the variable-interval component. If the stimulus was removed, then response rate was determined by the nature of the final component. Similar results were obtained in Experiments 2 and 3 with the use of a three-component tandem variable-ratio variable-interval variable-ratio schedule or tandem variable-interval variable-ratio variable-interval schedule. Thus, a brief stimulus that was not explicitly paired with reinforcement engendered behavior typical of the component schedule preceding its presentation.